Menyelidiki Hukum Pertanggungjawaban Pidana Partai Politik Terkait Tindak Pidana Korupsi - Moh. Fahri; Moh. Rusdiyanto U. Puluhulawa (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
The aim of this research is to find out criminal responsibility for political parties based on the perspective of responsibility theory and to find out the ideal sanctions for political parties that obtain funds from corruption. The research method used in this research is literature or normative, namely "the process of searching for a legal regulation , legal principles, and legal doctrine in order to answer the legal problems faced. The results and discussion of this research are: 1) Political parties that obtain funds from corruption crimes can be charged with legal responsibility, this is because political parties which are legal entities are included in the definition of corporations as intended in Law Number 8 of 2010 and Law Number 31 of 1999. Apart from that, the actions of political parties who receive funds from corruption crimes are also criminal acts of money laundering as stipulated in Law Number 8 of 2010. 2) The ideal sanction for political parties involved in or obtaining funds from corruption crimes is to reduce political party financial assistance sourced from the APBN/APBD by the amount 30%, this sanction is applied to political parties whose members commit criminal acts of corruption independently or singly and do not involve political parties and sanctions for the dissolution of political parties if they commit criminal acts of corruption collectively and/or political parties that receive funds from criminal acts of corruption.